2010
DOI: 10.1021/ja9088549
|View full text |Cite
|
Sign up to set email alerts
|

Designed Semisynthetic Protein Inhibitors of Ub/Ubl E1 Activating Enzymes

Abstract: Semisynthetic, mechanism-based protein inhibitors of ubiquitin (Ub) and ubiquitin-like modifier (Ubl) activating enzymes (E1s) have been developed to target E1-catalyzed adenylation and thioesterification of the Ub/Ubl C-terminus during the processes of protein SUMOylation and ubiquitination. The inhibitors were generated by intein-mediated expressed protein ligation, using a truncated Ub/Ubl protein (SUMO residues 1-94; Ub residues 1-71) with a C-terminal thioester, and synthetic tripeptides having a C-termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
95
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(95 citation statements)
references
References 35 publications
0
95
0
Order By: Relevance
“…To date inhibitors against two other E1 enzymes, the SUMO-1 activating enzyme (SAE) [125-127] and NEDD8 activating enzyme (NAE) have been developed [128]. NAE inhibition indirectly affects the UPS as NEDDylation is essential for the activation of the SCF (Skp, Cullin, F-box containing complex) Cullin-containing E3 complexes and thus represents a more specific approach than blocking UBE1.…”
Section: Introductionmentioning
confidence: 99%
“…To date inhibitors against two other E1 enzymes, the SUMO-1 activating enzyme (SAE) [125-127] and NEDD8 activating enzyme (NAE) have been developed [128]. NAE inhibition indirectly affects the UPS as NEDDylation is essential for the activation of the SCF (Skp, Cullin, F-box containing complex) Cullin-containing E3 complexes and thus represents a more specific approach than blocking UBE1.…”
Section: Introductionmentioning
confidence: 99%
“…This issue was resolved in part by utilizing synthetic adenylate analogs linked to SUMO and Ub to create structural analogs of the Ub/Ubl-adenylate. These adducts inhibit corresponding E1s, and the installation of an electrophilic trap at a position analogous to the carbonyl carbon of the C-terminal glycine successfully captured a cross-linked thioether E1 adduct that mimicks the tetrahedral intermediate during thioester bond formation (62). Subsequent structural studies using SUMO E1 with SUMO adenylate analogs revealed a new closed conformation wherein the E1 CYS domain rotates 130°, transiting the catalytic cysteine to a position proximal to the SUMO C-terminal adenylate analog that remains coordinated within a remodeled adenylate active site (Figure 1 c ) (70).…”
Section: E1 Ubiquitin-like Protein Activating Enzymesmentioning
confidence: 99%
“…A related concept has recently been applied to the study of E1 ubiquitin ligases (Lu et al, 2010; Olsen et al, 2010). These enzymes activate Ub and Ubls through adenylation (AMP) of their C-terminus followed by thioesterification of a conserved Cys residue in the enzyme.…”
Section: Site-specific Incorporation Of Unnatural Building Blocksmentioning
confidence: 99%
“…These enzymes activate Ub and Ubls through adenylation (AMP) of their C-terminus followed by thioesterification of a conserved Cys residue in the enzyme. To probe the first half-reaction, EPL was used to generate a reversible inhibitor by incorporating a non-hydrolyzable analog of AMP, 5‘- O -sulfamoyladenosine (AMSN), at the C-terminus of Ub and the Ubl, SUMO (Lu et al, 2010). A similar EPL approach was used to obtain a covalent inhibitor of the second half-reaction, in this case by incorporating a vinyl-sulfonamide electrophilic trap into the moiety (AVSN).…”
Section: Site-specific Incorporation Of Unnatural Building Blocksmentioning
confidence: 99%